Rectal Acetaminophen Improves Shunt Volume and Reduces Patent Ductus Arteriosus Ligation in Extremely Preterm Infants - Castaldo, Michael P.; Neary, Elaine; Bischoff, Adrianne R.; Resende, Maura H.F.; Weisz, Dany E.; Jain, Amish; Giesinger, Regan E.; McNamara, Patrick J. (American Journal of Perinatology, 2021)
Objective An alternative therapy for preterm infants with a hemodynamically significant patent ductus arteriosus (hsPDA) is needed when cyclooxygenase inhibitors fail or where treatment is contraindicated due to coexisting renal failure, necrotizing enterocolitis, and/or intestinal perforation. No studies have evaluated the efficacy of per rectum (PR) acetaminophen. The study aimed to evaluate the efficacy of PR acetaminophen in modulating the risk of PDA ligation.Study Design A retrospective matched case–control study was conducted to compare neonates born <29 weeks' gestation with evidence of hsDA, in an era when rescue rectal acetaminophen was used (January 2014–March 2018) as a treatment strategy, versus historical controls (July 2006–August 2012). All patients underwent comprehensive echocardiography assessment of ductal shunt volume according to a standardized protocol. Acetaminophen treated neonates were matched according to demographics, gestation, preintervention echocardiography features, and comorbidities. Control patients were selected when an echocardiography was performed at an equivalent postnatal age. Infants with a genetic syndrome, severe congenital malformation, or major forms of congenital heart disease excluding small atrial septal defect or ventricular septal defect, PDA, or patent formale ovale were excluded. The primary outcome was surgical ligation of the PDA. Secondary outcomes included echocardiography indices of hemodynamic significance, the composite of death, or severe BPD (defined by ventilator dependence at 36 weeks postmenstrual age). Descriptive statistics and univariate (t-tests, Fisher's exact test, and Mann–Whitney U test) analyses were used to evaluate clinical and echocardiography characteristics of the groups and compare outcomes.Results Forty infants (20 cases and 20 controls), with similar demographic and echocardiography features, were compared. Cases received 6.8 ± 0.7 days (60 mg/kg/day) of PR acetaminophen. Responders (n = 12, 60%) had echocardiography evidence of reduced ductal diameter (2.2 mm [1.9–2.6] to 1.1 mm [0–1.7], p = 0.002), left ventricular output (363 ± 108–249 ± 61 mL/min/kg; p = 0.002) and left atrium to aortic root ratio (1.7 ± 0.3–1.3 ± 0.2; p = 0.002) following treatment. The rate of PDA ligation was 50% lower (p = 0.02) and composite outcome of death or severe bronchopulmonary dysplasia was reduced (p = 0.04) in the acetaminophen group.Conclusion Rectal acetaminophen was associated with improvement in echocardiography indices of PDA shunt volume, a 50% reduction in PDA ligation rates and a reduction in the composite outcome of death or severe BPD. Pharmacologic and further prospective clinical studies are needed.Key Points
Keywords: patent ductus arteriosus; surgical ligation; acetaminophen; bronchopulmonary dysplasia; mortality